Vitamin D treatment distinctly modulates cytokine production by peripheral blood mononuclear cells among patients with chronic cardiac and indeterminate clinical forms of Chagas disease - Kamila Kássia dos Santos Oliveira; Diego José Lira Torres; Michelle da Silva Barros; Leyllane Rafael Moreira; Claudeir Dias da Silva Junior; Ana Karine de Araújo Soares; Maria da Piedade Costa Reis deAlbuquerque; Maria da Glória Aureliano Melo Cavalcante; Wilson Alves de Oliveira Junior; Michelle Christiane da Silva Rabello; Virginia Maria Barros deLorena (Immunity, Inflammation and Disease)
Abstract Introduction Chagas disease is caused by the protozoan Trypanosoma cruzi and is clinically divided into acute and chronic phases. Chronic Chagas cardiomyopathy is the most studied manifestation of the disease. Vitamin D deficiency has been suggested as a risk factor for cardiovascular disease. No studies demonstrate the action of this hormone in the cells of patients with chronic Chagas heart disease. Objective To evaluate the in vitro immunomodulatory effect of vitamin D on peripheral blood mononuclear cells of patients with the different chronic clinical forms of Chagas disease. Evaluating vitamin D's in vitro effect on blood cells by producing cytokines. Methods Thirteen patients of the undetermined form (IND), 13 of the mild cardiac form (CARD1) and 14 of the severe cardiac form (CARD2) of Chagas disease, and 12 with idiopathic heart disease (CARDid) were included. The cells obtained from peripheral blood were treated in vitro with vitamin D (1 × 10−7 M) for 24 h and cytokines were dosed in the culture supernatant. Results Although it was not possible to demonstrate statistically significant differences between the groups studied, our data showed that the cells treated with vitamin D modify (p < .05) the production of interferon‐γ (IFN‐γ) (decrease in IND), tumor necrosis factor‐α (TNF‐α) (decreased in CARD1 and CARDid), interleukin (IL)‐6 (increased in all groups), and IL‐10 (decreased in CARD1, CARD2, and CARDid) when compared to untreated cells. Conclusion In vitro treatment with vitamin D distinctly modulated the production of cytokines by mononuclear cells of peripheral blood among patients with chronic and indeterminate cardiac clinical forms of Chagas disease.